2015
DOI: 10.5483/bmbrep.2015.48.10.044
|View full text |Cite
|
Sign up to set email alerts
|

Antitcoagulant and antiplatelet activities of scolymoside

Abstract: Cyclopia subternata is a medicinal plant commonly used in traditional medicine to relieve pain. Here, the anticoagulant effects of scolymoside, an active compound in C. subternata, were examined by monitoring activated partial thromboplastin time (aPTT), prothrombin time (PT), and the activities of thrombin and activated factor X (FXa). The effects of scolymoside on plasminogen activator inhibitor type 1 (PAI-1) and tissue-type plasminogen activator (t-PA) expression were evaluated in tumor necrosis factor (TN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(16 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…Cell Culture: Primary HUVECs were obtained from Cambrex Bio Science Inc. (Charles City, IA) and maintained as previously described [40][41][42].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cell Culture: Primary HUVECs were obtained from Cambrex Bio Science Inc. (Charles City, IA) and maintained as previously described [40][41][42].…”
Section: Methodsmentioning
confidence: 99%
“…Animals and Husbandry: Male C57BL/6 mice (6-7-weeks old, weighing 27 g) purchased from Orient Bio Co. (Sungnam, Republic of Korea), were maintained as described previously [40][41][42].…”
Section: Methodsmentioning
confidence: 99%
“…Primary human umbilical vein endothelial cells (HUVECs) were purchased from Cambrex Corporation (Charles City, IA, USA) and maintained as previously described . Briefly, the cells were cultured to confluency at 37°C and 5% CO 2 in endothelial basal medium (EBM)‐2 basal media supplemented with growth supplements (Cambrex Bio Science, Charles City, IA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Thus, researchers are looking for new molecules with anticoagulant and/or antiplatelet effects able to improve therapies, but without restrictions or limitations. Lot of molecules derived from natural sources, be it from terrestrial or marine environment, have shown antihemostatic effects (Pimentel et al, 2003;de Andrade et al, 2011;Yoon et al, 2015;Lorigooini et al, 2015). Nonetheless, as known, most products with a clinical or medical interest came from oceans, approximately 33 and 25% from sponges and algae, respectively (Kijjoa and Sawangwong, 2004;Newman and Cragg, 2012).…”
Section: Effect Of the Extracts Of A Spicifera On Platelet Aggregationmentioning
confidence: 99%